2017
DOI: 10.3390/ijerph14091043
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Vitamin A on Fracture Risk: A Meta-Analysis of Cohort Studies

Abstract: This meta-analysis evaluated the influence of dietary intake and blood level of vitamin A (total vitamin A, retinol or β-carotene) on total and hip fracture risk. Cohort studies published before July 2017 were selected through English-language literature searches in several databases. Relative risk (RR) with corresponding 95% confidence interval (CI) was used to evaluate the risk. Heterogeneity was checked by Chi-square and I2 test. Sensitivity analysis and publication bias were also performed. For the associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
30
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 63 publications
(149 reference statements)
3
30
5
Order By: Relevance
“…Our findings were consistent with the results of a previous meta-analysis published by Xu et al 11 , who found that a high intake of dietary β-carotene was significantly decreased the risk of hip fracture by 28% (OR 0.72; 95% CI: 0.54-0.95). However, our findings were contradicted with recent meta-analysis 38 , which revealed that higher β-carotene intake was weakly associated with the increased risk of total fracture (RR 1.07;…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our findings were consistent with the results of a previous meta-analysis published by Xu et al 11 , who found that a high intake of dietary β-carotene was significantly decreased the risk of hip fracture by 28% (OR 0.72; 95% CI: 0.54-0.95). However, our findings were contradicted with recent meta-analysis 38 , which revealed that higher β-carotene intake was weakly associated with the increased risk of total fracture (RR 1.07;…”
Section: Discussioncontrasting
confidence: 99%
“…95% CI: 0.97, 1.17). The difference can be explained by a limited number of studies included for both total fracture and hip fracture risk by Zhang et al 38 , in their studies all sources of beta-carotene such as serum, plasma, and dietary intake were analyzed together.…”
Section: Discussionmentioning
confidence: 99%
“…This may be a plausible result given hormonal differences between sexes. These results provide additional information beyond those published by the two meta-analyses [16,45] that reported a null association between β-carotene intake and fracture risk in females, but not in males. Differing conclusions in sub-analyses by geographic region for the relationship between dietary β-carotene and factures are likely due to variations in the study populations, speci cally with regard to genetics, diverse dietary habits that may be tailored to each culture, and lifestyle factors.…”
Section: Discussionsupporting
confidence: 55%
“…Our ndings were consistent with the results of a previous meta-analysis published by Xu et al [16] that concluded high intake of dietary β-carotene signi cantly decreased the risk of hip fracture by 28% (Odds Ratio [6] 0.72; 95% CI: 0.54-0.95). However, ndings from the present meta-analysis were discordant with the recently published meta-analysis published by Zhang et al [45], which observed that higher β-carotene intake was weakly associated with the increased risk of total fracture (RR 1.07; 95% CI: 0.97, 1.17), though the results were not statistically signi cant. The differences in the ndings between our study and Zhang et al's may be due to the lower number of studies included by Zhang et al [45].…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation